1998
DOI: 10.1021/jp980860q
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Atomic Hydrogen Induced Carbon−Carbon Bond Activation in Cyclopropane on the Pt(111) Surface

Abstract: Carbon-carbon bond activation in adsorbed cyclopropane is observed following exposure to gas-phase atomic hydrogen on the Pt(111) surface for temperatures as low as 120 K despite the fact that this low index platinum surface generally does not activate C-C bonds. Cyclopropane desorbs molecularly at 140 K. In the presence of coadsorbed hydrogen, no reaction with cyclopropane is observed. In contrast, gas-phase atomic hydrogen reacts with cyclopropane at 120 K to form a propyl intermediate. During subsequent hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Synthesis of new transition metal hydrides and hydrogen complexes and understanding their structures and bonding are of fundamental importance for new hydrogen-storage materials and for use in the activation of H–H, C–H, and C–C bonds. For example terminal tantalum hydrides are extremely reactive, and they can reduce CO 2 to form bridging methylene diolate complexes . Pulse-laser ablation is one of the most promising methods to generate metal polyhydrides and complexes from reactions of reactive metal atoms with H 2 . Many transition metal hydrides, lanthanide hydrides, and actinide hydrides and their hydrogen complexes have been synthesized for infrared investigation in this research laboratory. …”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of new transition metal hydrides and hydrogen complexes and understanding their structures and bonding are of fundamental importance for new hydrogen-storage materials and for use in the activation of H–H, C–H, and C–C bonds. For example terminal tantalum hydrides are extremely reactive, and they can reduce CO 2 to form bridging methylene diolate complexes . Pulse-laser ablation is one of the most promising methods to generate metal polyhydrides and complexes from reactions of reactive metal atoms with H 2 . Many transition metal hydrides, lanthanide hydrides, and actinide hydrides and their hydrogen complexes have been synthesized for infrared investigation in this research laboratory. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the large potential energy associated with the unpaired electron, gas-phase hydrogen radicals react with adsorbates that do not react with adsorbed hydrogen . Hydrogen radicals have been used in a wide range of reactions including carbon−carbon bond activation in adsorbed cyclopropane, hydrogenation of CC bonds in adsorbed cyclohexene and ethylene, reduction of adsorbed nitrogen to form ammonia, and abstraction of surface carbon through methanation . In addition, gas-phase hydrogen radicals have been shown to populate subsurface hydrogen states in nickel surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…Because gas phase atomic hydrogen is 218.4 kJ/mol more energetic than molecular hydrogen (1/2 dissociation energy of H 2 ), when interacting with Pt(111), gas phase atomic hydrogen is energetic enough to overcome any activation energy to form all likely adsorbed H ad species (surface H ad species and bulk H ad species), surely including the active species for practical catalytic reactions. Gland et al [21][22][23][24][25] found that gas phase atomic hydrogen can undergo ring-opening reaction directly with cycloalkanes adsorbed on metal single crystal surfaces and that the ring-opening reaction follows Eley-Rideal mechanism. Therefore, even under UHV conditions, interaction of gas phase atomic hydrogen with Pt(111) can lead to the formation of detectable bulk H ad species.…”
Section: Resultsmentioning
confidence: 97%